The Urgency of Contemporary Era Science Education in Islam - Agus Mailana; Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2024)
Every individual has personal potential according to the theory of multiple intelligences. For this reason, it is necessary to strengthen scientific aspects to sharpen the potential of reason and efforts to Islamize science, as well as the demands of the 21st century. This research aims to analyze the urgency of educational science in the contemporary era in Islam. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible websites such as Google Scholar and SINTA. Then the data were analyzed and checked for validity through data triangulation. The results of this study conclude that the urgency of science in the contemporary era in Islam; the first is interpreted as an answer to the demands of 21st century science; second, increasing the potential of the human mind in realizing renewal (innovation); third, exploring the multiple intelligence potential of each student; and fourth, strengthening efforts to Islamize knowledge through proving the scientific process.